THE EFECTS OF COGNITIVE REMEDIATION THERAPY IN BIPOLAR DISORDER PATIENTS - Cahya Pandya Astami (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Background: Bipolar Disorder (BD) is a mental disorder impacting 45 million people worldwide. BD patients often experience persistent cognitive impairments. These cognitive impairments can impact psychosocial outcomes and reduce employment. Cognitive remediation (CR) is a behavioral training-based intervention that points to help cognitive processes and improve functional outcomes. The effects of CR in BD are inconclusive. Some studies claimed that CR could improve many cognitive domains and increase Quality of Life, but other study claims that CR didn't improve overall cognitive and psychosocial functioning. In this paper, we aim to explore the effect of CR in BD patients. Objective: To understand the effects of cognitive remediation therapy in bipolar disorder patients. Methods: The author tried to explore all the papers in English published from 2018 to 2022. The electronic databases used are Google Scholar, ScienceDirect, Elsevier, Wiley Library, PubMed, and Cochrane. Two sets of keyword search algorithms were used with Boolean operator AND. The first keyword was "bipolar disorder" and the second was "cognitive remediation". Then we included all publications that covered the effects of CR in BD. Results: Involvement all cogntivie domains need to be evaluate first before bring cognitive remediation therapy. Follow up on their quality of life, function memory recall and brain function, event the patient can still need to be evaluate with antipsychotic or mood stabilizer drugs.. Conclusion: CR has some effects in BD patients related to multiple cognitive domains (global cognition, executive function, attention, learning, and memory), IQ, psychosocial functions, functional outcomes, and goal attainment. More high-quality randomized trials with objective cognitive impairments as inclusion criteria of the participants, the longer intervention of CR, better control of biases, language and perceptual-motor function observed, and bigger sample size are required.  Keywords: cognitive function, cognitive remediation, bipolar disorder.